Selection of rice aroma from crossing aromatic rice x T250.7 mutant genotype using DNA marker - ISHAK ISHAK; FLOREAN FEDORA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ishak I, Fedora F. 2024. Selection of rice aroma from crossing aromatic rice x T250.7 mutant genotype using DNA marker. Biodiversitas 25: 2191-2197. Breeding fragrant rice using conventional approach was considered ineffective due to time consuming, therefore molecular breeding using DNA markers was introduced. This research aimed to utilize marker-assisted selection (MAS) for detection of fragrance gene in rice related to molecular breeding. Crossing between aromatic rice (Sinar 1) and non-aromatic rice (T250.7 mutant genotype) showed the results at F1 plants and found the DNA fragment size of 257 bp for fragrance genes in rice was at TS1, TS2, TS3, TS4, TS5, and TS.7 genotypes, whereas, TS6 did not show a fragment DNA at 257 bp. It was predicted that the TS6 genotype did not cross between variety Sinar 1 with T250.7. The F2 seeds were selected and morphologically, they had slender seeds and continued planting for F2 plants. Based on DNA marker identification, it revealed that 75% of the rice plants carried aroma. Similarly, the selected F3 plants continued to be planted and molecular identification indicated that aroma segregation was the same as that in the previous generation. Plants with the number of accessions of 721, 761, and 7210 were predicted to have homogeneity in aroma after detection using molecular markers. The MAS in breeding programs can shorten the duration of rice selection.